2013
DOI: 10.1159/000345891
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Response Assessment of Transcatheter Arterial Chemoembolization for Hepatocellular Carcinoma: Ultrasonography, CT and MR Imaging

Abstract: Two randomized controlled trials identified that transcatheter arterial chemoembolization (TACE) for hepatocellular carcinoma (HCC) shows a significant survival benefit compared with controls, after a long-term controversy. Thus, TACE is the current standard of care for patients presenting with multinodular HCC. Monitoring tumor response to TACE is part of the clinical management of HCC patients. Imaging, including ultrasonography, computed tomography and magnetic resonance imaging, has an important role in as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 95 publications
0
16
0
Order By: Relevance
“…We regarded lipiodol accumulation in targeted tumors seen on CT scans as indicating necrosis. This was due to the fact that it had been previously reported in several studies that the lipiodol retention areas observed on CT corresponded to necrotic areas (25)(26)(27). Complete response (CR) was defined as the disappearance of all targeted tumors or 100% tumor necrosis, partial response (PR) was defined as a ≥50% reduc-tion in tumor size and/or necrosis, and progressive disease (PD) was defined as >25% tumor enlargement and/or the appearance of any new HCC tumors.…”
Section: Methodsmentioning
confidence: 88%
“…We regarded lipiodol accumulation in targeted tumors seen on CT scans as indicating necrosis. This was due to the fact that it had been previously reported in several studies that the lipiodol retention areas observed on CT corresponded to necrotic areas (25)(26)(27). Complete response (CR) was defined as the disappearance of all targeted tumors or 100% tumor necrosis, partial response (PR) was defined as a ≥50% reduc-tion in tumor size and/or necrosis, and progressive disease (PD) was defined as >25% tumor enlargement and/or the appearance of any new HCC tumors.…”
Section: Methodsmentioning
confidence: 88%
“…is useful for diagnosing residual and recurrent tumors in HCC cases after Lp-TACE, because Lipiodol has been thought not to affect MRI signal intensity [17][18][19] . However, some studies have suggested that Lipiodol itself induces MRI signal changes with normal imaging methods, possibly due to its oil-based nature 7,8 , while other reports indicate that Lipiodol hardly affects MRI signals [9][10][11][12] .…”
Section: Discussionmentioning
confidence: 99%
“…CT is also useful in the post-Lp-TACE management of HCCs 15,16 . However, once a high density of Lipiodol has accumulated in the tumor, evaluating whether tumor-enhancing effects are present by contrast-enhanced CT and diagnosing residual or recurrent tumors can be dif cult 17,18 . It is also worth noting that artifacts are created when…”
Section: Originalmentioning
confidence: 99%
See 1 more Smart Citation
“…By referring to the doses used in systemic chemotherapy, traditional TACE performs embolization after intra-arterial infusion plus chemotherapy drugs in terms of chemotherapy drug doses (Cui et al, 2012;Kong et al, 2012;Minami et al, 2013;Murata et al, 2013;Wang et al, 2013). It is still controversial with regard to chemotherapy drug doses at present.…”
Section: Discussionmentioning
confidence: 99%